(untitled) (Journal of Society of Surgeons of Nepal, 2016)
Introduction and Objective: Hydatid cyst of the liver is a fairly common parasitic condition. We present here a series of 9 patients with hydatid cyst of the liver managed by minimally invasive surgery Materials and Methods: It was a prospective study in patients presenting with hydatid cyst of the liver to Surgery Department who were managed laparoscopically from January 2013 to November 2015. Result: There were 9 patients (5 males and 4 females). The mean operative time was 124+32 minutes. One patient developed mild allergy in the form of skin rashes on 3rd postoperative day, and another patient developed cholangitis which resolved on conservative management. There was no conversion. Conclusion: Laparoscopic management of hydatid cysts is possible, and looks promising provided we have advanced energy sources.